Handbook of Targeted Cancer Therapy and Immunotherapy - Karp, Daniel D. (Wolters Kluwer, 2018)
"The exponential growth of oncology drug development and personalized/targeted therapy in the recent years has presented a challenge to even the most experienced cancer researchers. Many of us struggle to keep up with the hundreds of clinical trials conducted each year. To help with this challenge, we present here the second edition of our concise handbook intended to make the results of clinical trials of targeted cancer treatments and immunotherapy more easily accessible to cancer researchers and clinicians. We are very proud of the reception the first edition received from oncologists, medical staff, students, and even patients, and we are excited about the updated and widely expanded content included in this second edition"--Provided by publisher.